Global Research Trends on Creative Industry Competitiveness: A Bibliometric Analysis of Innovation and Sustainability - Dimas Ramadan; Agung Utama (Economic and Business Horizon, 2026)
The creative industry has emerged as a strategic driver of economic growth and competitiveness. This study aims to analyze the global development, research patterns, thematic structures, and future directions of studies on creative industry competitiveness through a bibliometric approach. The study employed a bibliometric literature review using publications indexed in the Scopus database, with data analyzed through VOSviewer to examine publication trends, authorship, institutional and country contributions, keyword co-occurrence, and thematic clustering. The findings reveal a substantial increase in scientific publications over time, reflecting growing academic interest in creative industry competitiveness. China and Indonesia emerged as leading contributors, while journal articles dominated the publication types, confirming the maturity of the field. Keyword network analysis identified seven major thematic clusters encompassing strategic management, innovation, sustainability, entrepreneurship, digital transformation, cultural heritage, regional development, and SME competitiveness. These findings indicate that research on creative industry competitiveness has evolved into a multidisciplinary domain characterized by strong interconnections among technological, organizational, and institutional dimensions. The study concludes that future research should adopt more integrated approaches by incorporating emerging themes, such as artificial intelligence, platform ecosystems, green innovation, and the circular economy, to strengthen the sustainable competitiveness of creative industries.